Heterogeneity in BMI Percentile and Weight Status Among Asian American Youth - Darcy M. Van Deventer, BS; Margo A. Sidell, SCD; Catherine Lee, PhD; Deborah R. Young, PhD; Monique M. Hedderson, PhD; Deborah A. Cohen, MD, MPH; Emily F. Liu, MPH; Lee J. Barton, MS; Galina Inzhakova, MPH; Bing Han, PhD (AJPM Focus)
Introduction: There are important and understudied health differences among subgroups of Asian Americans. The authors examined differences in BMI percentile and body weight status among Asian American youth. Methods: The authors conducted a retrospective cohort study using electronic health records in 2011–2020 from 2 integrated healthcare systems in California. Single-race, non-Latino White, and Asian American youth aged 2–19 years during the study period were included. Asian American subgroups included East, South, Southeast, and unidentified. Whites were the reference group. Study outcomes included age- and sex-specific BMI percentile and body weight status category (underweight, overweight or obesity, obesity). Series of 1-sample estimates for study outcomes were calculated by calendar year and biological ages. Results: A total of 395,134 youth were included in the study (mean [SD] age at baseline of 8.26 [5.61] years; mean [SD] BMI percentile of 53.8 [30.3]), including 23,183 East Asians; 34,783 South Asians; and 34,738 Southeast Asians. Southeast Asians had the highest age-adjusted prevalence of obesity (2019 estimate: 13.3%) than East Asians (5.2%), South Asians (7.8%), and Whites (11.8%). South Asians had the highest prevalence of underweight (2019 estimate: 11.8%) than East Asians (5.5%), Southeast Asians (3.9%), and White (3.6%). Conclusions: Substantial heterogeneity among Asian American youth was found in the study cohort. Asian American youth face distinct challenges of unhealthy weight statuses unique to their subgroups.